2005
DOI: 10.1021/ac051405a
|View full text |Cite
|
Sign up to set email alerts
|

Nanovolume Kinase Inhibition Assay Using a Sol−Gel-Derived Multicomponent Microarray

Abstract: We report on the development of a new class of kinase microarrays based on the coimmobilization of both kinase and substrate components within a single pin-printed sol-gel microarray element and the use of such arrays for nanovolume inhibition assays. We successfully immobilized the alpha-catalytic subunit of cAMP-dependent protein kinase (PKA) and the peptide substrate kemptide within sol-gel-derived microarrays for the purpose of monitoring phosphorylation and inhibition. Using Pro-Q Diamond stain as an end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…microarrays, 26 using nanoliter-volume assays 14,27 and highly parallel screening. 28 An emerging functional protein microarray platform involves the pin-printing of protein-doped silica sols onto functionalized surfaces.…”
mentioning
confidence: 99%
“…microarrays, 26 using nanoliter-volume assays 14,27 and highly parallel screening. 28 An emerging functional protein microarray platform involves the pin-printing of protein-doped silica sols onto functionalized surfaces.…”
mentioning
confidence: 99%
“…Martin et al described the Pro-Q diamond phospho-sensor dye which recognises phosphopeptides with remarkably little cross reactivity and a low false-negative rate [142]. It was demonstrated that this dye could be applied to kinase profiling [97,143,144] and phosphatase profiling [74,75] using high density peptide microarrays. A very similar approach was reported using biotinylated zinc(II) chelate phosphate sensor N-(5-(2-(?…”
Section: Assays and Detectionmentioning
confidence: 99%
“…Nevertheless, a number of recent promising studies have used Pro-Q DPS for the detection of phosphorylation events on microarrays (Rupcich et al 2005;Pal et al 2006). The first attempts to detect phosphorylation status and kinase activity on microarrays using fluorescence detection were made by using ProQ-Diamond phosphoprotein strain (Pro-Q DPS).…”
Section: Establishment Of Protein Microarrays For Phosphorylation Stumentioning
confidence: 99%